PENERAPAN STRATEGI THINK TALK WRITE DAN TEKNIK PEER CORRECTION UNTUK MENINGKATKAN KETERAMPILAN MENULIS IKLAN - Lestari, Indah; Iswara, Prana Dwija; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2019)
The research conducted in VB class of East Palimanan 1 Elementary School was motivated by the conditions in the learning of advertisements writing skills that were still low on the elements of the advertisement sentence. To overcome the difficulties of students in writing advertisements, an increase is made by applying the think talk write strategies and peer correction techniques. This research was conducted using the class action research method, with a research design model from Kemmis and Mc. Taggart. Data collection techniques used were interviews, observations, learning outcomes tests, and field notes. Student learning outcomes in this study assessed advertisements that were in accordance with the elements of advertisement, advertisement language and choice of words, advertisement images, in the first cycle students completed 15 (60%) students, the second cycle reached 19 (76%) students, and the third cycles reached 23 (92%) students who complete.